A thalassaemia intermedia case with concomitant left atrial thrombus. (20th June 2014) - Sahin, Cem; Basaran, Ozcan; Topal, Yasar; Akin, Fatih
Abstract : Although marked improvements have been observed in the life expectancy of patients with thalassaemia by regular blood transfusion and strict iron chelation therapies in recent years, these patients still have to deal with several complications, mainly cardiovascular. One of the life-threatening complications is the chronic hypercoagulable state and thromboembolic events which develop due to haemostatic alterations in patients with thalassaemia, although they are more frequently seen in those with thalassaemia intermedia. Many thromboembolic complications, mainly deep venous thrombosis and cerebral thrombosis, have been reported in thalassaemia. However, intracardiac thrombosis is rarely seen. In this manuscript, we presented a case that underwent splenectomy 6 years ago but not regularly attended the control visits and presented to our clinic with gradually increasing exercise dyspnoea for 2 months.